Pengaruh Debt to Equity Ratio, Gross Profit Margin, Perputaran Piutang, dan Return on Equity terhadap Nilai Perusahaan pada Perusahaan Consumer Goods di Bursa Efek Indonesia Tahun 2018 – 2020 - Jason Valerio Hendry; Friska Darnawaty Sitorus; Venny Venny (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this research is to analyze the effect of  the Debt to Equity Ratio (DER), Gross Profit Margin (GPM), Accounts Receivable Turnover (PP), and Return on Equity (ROE) have on the value of existing companies as Consumer Goods companies on the Indonesia Stock Exchange ( IDX) in 2018-2020. This research will use a quantitative approach. The population is the Consumer Goods sector companies listed on the Indonesia Stock Exchange in 2018-2020, totaling 57 companies. Sampling using purposive sampling method, and resulted in a number of 31 companies. By using analysis technique with multiple linear regression test.The results of this research show that the Debt to Equity Ratio (DER) is not partially affected by the value of consumer goods companies listed on the Indonesia Stock Exchange in 2018 - 2020. Gross Profit Margin (GPM) is partially affected by the value of consumer goods companies listed on the Stock Exchange. Indonesia in 2018 - 2020. Accounts Receivable Turnover (PP) has no partial effect on the value of consumer goods companies listed on the Indonesia Stock Exchange in 2018-2020. Return on Equity (ROE) has no partial effect on the value of consumer companies goods that have been listed on the Indonesia Stock Exchange in 2018-2020. Debt to Equity Ratio, Gross Profit Margin, Accounts Receivable Turnover, and Return on Equity are very influential simultaneously on the value of consumer goods companies listed on the Indonesia Stock Exchange in 2018 - 2020.